2019
DOI: 10.1136/bmj.l1161
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cervical disease at age 20 after immunisation with bivalent HPV vaccine at age 12-13 in Scotland: retrospective population study

Abstract: Objective To quantify the effect on cervical disease at age 20 years of immunisation with bivalent human papillomavirus (HPV) vaccine at age 12-13 years. Design Retrospective population study, 1988-96. Setting National vaccination and cervical screening programmes in Scotland. Participants 138 692 women born between 1 January 1988 and 5 June 1996 and who had a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
171
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(190 citation statements)
references
References 34 publications
14
171
0
5
Order By: Relevance
“…Compared both to previous reports of population‐based, type‐specific HPV prevalences in the same country and global meta‐analyses where HPV16 and 18 are the dominant causes of high‐grade CIN, it is remarkable that we find that the major oncogenic vaccine‐targeted HPV types 16 and 18 are now almost nonexistent among young vaccinated women in Sweden—even among those women who develop CIN. A recent evaluation of effectiveness of another HPV vaccine, Cervarix, demonstrated a strong reduction in prevalence of cervical disease (CIN1–3) and an obvious herd protection of those women who were not immunized . The contrast between increasing prevalence of low‐grade cytological abnormalities and declining low‐grade histological abnormalities (CIN1) implies low progressive potential of detected lesions, which is in line with our findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Compared both to previous reports of population‐based, type‐specific HPV prevalences in the same country and global meta‐analyses where HPV16 and 18 are the dominant causes of high‐grade CIN, it is remarkable that we find that the major oncogenic vaccine‐targeted HPV types 16 and 18 are now almost nonexistent among young vaccinated women in Sweden—even among those women who develop CIN. A recent evaluation of effectiveness of another HPV vaccine, Cervarix, demonstrated a strong reduction in prevalence of cervical disease (CIN1–3) and an obvious herd protection of those women who were not immunized . The contrast between increasing prevalence of low‐grade cytological abnormalities and declining low‐grade histological abnormalities (CIN1) implies low progressive potential of detected lesions, which is in line with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Strategies for surveillance/monitoring of HPV vaccination programs have commonly involved following the statistics of CIN lesions detected by screening in highly vaccinated cohorts. 19,27,30 Our data imply that this is insufficient as mere registry data on the occurrence of CIN lesions will not capture if their progressive potential has changed. Our data finding that HPV 16/18 has almost disappeared as a cause of CIN among young vaccinated women in Sweden suggests that the CIN lesions that are still diagnosed in this cohort have lower progressive potential.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In a linked paper, Palmer and colleagues (doi:10.1136/bmj.l1161) report findings from Scotland, where the combination of high coverage with bivalent HPV vaccine, young age of screening initiation, and high quality individual level data across the population, unequivocally show high vaccine effectiveness in young women against high grade cervical disease regardless of causal HPV type 4…”
mentioning
confidence: 99%
“…All countries must now consider how they can best implement and evaluate vaccination, screening, and treatment programmes that support the World Health Organization’s call for elimination of cervical cancer as a public health problem 7. Scotland has shown that integrated registry systems are highly effective tools in achieving and evaluating high vaccine uptake,8 and in assessing subsequent outcomes,4 including screening performance 9…”
mentioning
confidence: 99%